The Phoneme and its manifestations in the Holy Quran in narrated by Ḥafṣ according to ϽAaṣim, AL-Baqarah chapter as Example. - Bassam Musbah Aghbar (My University, 2014)
This research, a phonetic study, deals with the most eloquent text, known by humankind i.e. the Holy Quran. It studies the first brick of which any text is built i.e. the sounds which together constitute words; words constitute sentences, and these constitute texts. The research has the title " The Phoneme and its manifestations in the Holy Quran in narrated by Ḥafṣ according to ϽAaṣim, AL-Baqarah chapter as Example ". Depending on the historical and descriptive methods, the study is composed of two studies: a theoretical study of the phoneme aiming at determining the rules and principles, and an applied study aiming at showing its manifestations, formations, variations and features. The study, accompanied by statistical tables and graphs, is applied to the Holy Quran, from which the largest chapter was selected So that the conclusion can be generalized, with most probability, to the whole Quran, and be considered as general principles, taxing into consideration that this chapter contains all the phonemes of Arabic and their different manifestations. The study followed the proper scientific method of research, containing: a preface, an introduction, and four chapters, as follows: • The introduction: discusses at-tajweed science: definition, origin, and relation with phonetics. • The first chapter: discusses the Quranic qira'aat, the difference between them and the seven letters, the most famous qira'aat of the Holy Quran, the characteristics of the qira'ah of Ḥafṣ according to ϽAaṣim in particular. • The second chapter an abridged study of the segmented phoneme with its types, schools of study, and also the supersegmental phoneme, with its two most prominent types according to semantic effects, i.e. the phoneme intonation and juncture. • The third chapter: the segmental phoneme and its manifestations; this is the largest chapter, having the formed a practical applied study, discussing the rules that govern the consonant phonemes of n and m the phonemes of qalqalah, emphatic and non emphatic pronunciation of latters. • The fourth chapter: the supersegmental phoneme and its manifestations, a practical chapter also, in which phonemes of intonation and juncture and their manifestation in the cow chapter. The Holy Quran were studied. • Lastly: the final part, gives the most prominent conclusions and remarks obtained by the study.

يُعدُّ هذا البحث، دراسة لغوية صوتية، تتناول أبلغ نص عرفته البشرية، وهو القرآن الكريم، وهو يعالج، اللبنة الأولى لأي نص، ألا وهي الأصوات التي تتآزر لتؤلف كلمات، ومن الكلمات جملا، ومن الجمل نصوصاً، وكان عنوان هذا البحث :"الفونيم وتجلياته في القرآن الكريم برواية حفص عن عاصم، سورة البقرة نموذجا"، ودرسنا فيه، معتمدين المنهجين، التاريخي، والوصفي، الفونيم دراسة نظرية، لمعرفة أسسه، وقواعده، ودراسة تطبيقية، لمعرفة تجلياته، وتشكلاته، وصوره، وملامحه، وجاءت هذه الدراسة المشفوعة بالجداول الإحصائية، والرسوم البيانية، دراسة تطبيقيةً على القرآن الكريم، الذي اخترنا منه أكبر سورة فيه، وهي سورة البقرة، حتى نخرج بملحوظات، هي أشبه بالنتائج التي يمكن تعميمها على القرآن الكريم كلّه، وتقعيدها، كيف لا؟ وهذه السورة تحتوي، كغيرها من السور القرآنية، على فونيمات العربية كافة، وتجلياتها المختلفة. وحتى يسير هذا البحث على النهج العلمي الصحيح، فقد جاء مكوناً من مقدمة، وتمهيد، وأربعة فصول، على النحو الآتي: • التمهيد: تحدث عن علم التجويد، تعريفاً ونشأة، وعلاقته بعلم الأصوات. • الفصل الأول: تناول مصطلح القراءات القرآنية، والفرق بينه وبين الأحرف السبعة، وأشهر القراءات القرآنية، ومزايا قراءة حفص عن عاصم، بوجه خاص. • الفصل الثاني: دراسة موجزة لنظرية الفونيم القطعي، ومعرفة أنواعه، ومدارسه، ومكوناته، ودراسة الفونيم فوق القطعي أيضاً، وأبرز نوعين فيه، لما لهما من تأثير دلالي، وهما فونيما التنغيم، والمفصل. • الفصل الثالث: الفونيم القطعي وتجلياته، وهو أكبر فصول الدراسة، وقد اتخذ شكل دراسة عملية تطبيقية، واشتمل على دراسة أحكام كل من فونيم النون الساكن، وفونيم الميم الساكن، وفونيمات القلقلة، والترقيق، والتفخيم. • الفصل الرابع: الفونيم فوق القطعي، وتجلياته، وهو فصل عملي، أيضاً، وتمت فيه دراسة كل من فونيم المفصل، وفونيم التنغيم وتجلياتهما في سورة البقرة. • وأخيراً: جاءت خاتمة البحث، التي احتوت أبرز النتائج والملحوظات التي توصل إليها البحث.
الفونيم وتجلياته في القرآن الكريم برواية حفص عن عاصم، سورة البقرة نموذجاً.